Mutual fund shareholder letters: Flows, performance, and managerial behavior - Alexander Hillert; Alexandra Niessen-Ruenzi; Stefan Ruenzi (Leibniz Institute for Financial Research SAFE, 2023)
Fund companies regularly send shareholder letters to their investors. We use textual analysis to investigate whether these letters' writing style influences fund flows and whether it predicts performance and investment styles. Fund investors react to the tone and content of shareholder letters: A less negative tone leads to higher netflows. Thus, fund companies can use shareholder letters as a tactical instrument to influence flows. However, at the same time, a dishonest communication that is not consistent with the fund's actual performance decreases flows. A positive writing style predicts higher idiosyncratic risk as well as more style bets, while there is no consistent predictive power for future performance.
Keywords: G23; G11; 330; Fund Flows; Textual Analysis; Shareholder Letters; Investment Styles